Review and update on the use of the microanastomotic coupler device for arterial anastomosis in free tissue transfer - El Baba, B.; Watfa, W.; Youssef, L.; Di Summa, P. G.; Bou Khalil, P.; Jurjus, A. R.; Loyens, D. B.; Sertel, Serkan; Jurjus, R. A. (The British journal of oral & maxillofacial surgery, 2021)
While a simple interrupted sutured anastomosis remains the gold standard in microsurgery, the introduction of the microanastomotic coupler device (MACD) has decreased procedure time and thrombosis risk, and improved the patency of venous anastomoses. The aim of this review is to update the evidence-based advantages of the MACD on arteries, based on clinical and experimental data, and to compare them to the hand-sewn approach in free flap transfer. All relevant articles that appeared in the PubMed and Medline/Ovid databases during the past three decades were reviewed. After exclusions, 11 studies were retained and discussed. The MACD had a generally shorter arterial anastomosis time, with improved flap survival and reduced ischaemia compared with the hand-sewn approach. The use of the MACD in arterial anastomosis is an efficient and less time-consuming alternative to the hand-sewn technique, provided that the selection of vessels is appropriate and the vessel diameter is large enough to do the anastomosis.
Available online 1 July 2020
Gesehen am 04.03.2021